2017
DOI: 10.1080/03630242.2017.1292344
|View full text |Cite
|
Sign up to set email alerts
|

Muslim women’s perspectives on designing mosque-based women’s health interventions—An exploratory qualitative study

Abstract: Mosques could serve as a promising setting for health interventions. However, little empirical data are available to guide the development of mosque-based health interventions, especially for women. We aimed to assess Muslim women's views on effective strategies for mosque-based educational interventions to promote women's health. A sample of Muslim women of diverse ethnicity and race was recruited from mosques in Chicago to participate in semi-structured interviews. In interviews, nineteen participants (aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 20 publications
(29 reference statements)
5
40
0
Order By: Relevance
“…One study, which assessed the feasibility of developing (in coproduction with resident imams) and delivering tailored sermons (included theologically framed health messaging), found that the intervention was well received by all members of the mosque community . These findings support those of recent studies that suggest that strategies for leveraging religious concepts to promote health among Muslims have value …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…One study, which assessed the feasibility of developing (in coproduction with resident imams) and delivering tailored sermons (included theologically framed health messaging), found that the intervention was well received by all members of the mosque community . These findings support those of recent studies that suggest that strategies for leveraging religious concepts to promote health among Muslims have value …”
Section: Discussionsupporting
confidence: 56%
“…3 These findings support those of recent studies that suggest that strategies for leveraging religious concepts to promote health among Muslims have value. 40,41 Most of the interventions we identified were inspired and run by recruitment method was via announcements after prayers, and faith leaders appear supportive of health promotion interventions. This method of recruitment appears to promote a relatively high reach (recruitment and retention rate), which in turn may militate against intervention-generated inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a religiously tailored program in a mosque‐based education intervention on mammography screening in the USA facilitated increased usage and intended usage of mammography screening among Muslim women . In a qualitative study involving Muslim American women, health messaging delivered by Imams and peer educators in concordance with Islamic principles was seen as an effective modality to increase acceptance in community members . The impact and positive perception of such interventions indicates that beginning the promotion of organ donation in mosques, done in collaboration with religious leaders and done so in a religiously tailored manner, may prove to be beneficial and effective .…”
Section: Discussionmentioning
confidence: 99%
“…In order to enhance the acceptability of the testing campaigns, we propose also a series of awareness campaigns at the Pakistani mosque (located in the suburb close to the hospital) during celebrations, with the support of the mosque association and Urdu-speaking local doctors. A growing body of literature, especially in the UK and USA, mentions the usefulness of including faith-based organizations in the health promotion interventions, given the strong collectivism and faith-based values of South Asian communities ((40)(41)(42). We already engaged with the local Pakistani mosque leaders, with the help of participants, and agreed on future collaborations.…”
mentioning
confidence: 99%